Comparison of Pesticide Residue Levels in Red Wines from Canary Islands, Iberian Peninsula, and Cape Verde - Álvaro Santana-Mayor; Ruth Rodríguez-Ramos; Bárbara Socas-Rodríguez; Carlos Díaz-Romero; Miguel Ángel Rodríguez-Delgado (Foods, 2020)
In this work, the QuEChERS method coupled to liquid chromatography-time-of flight-mass spectrometry and gas chromatography-triple quadrupole-mass spectrometry were applied for the evaluation of pesticide residues and risk assessment in red wines. The methodologies were successfully validated for 173 pesticides. Recovery values were in the range 75–100% for almost all pesticides and limits of quantification were between 2.60 and 21.39 µg/kg, which are in good agreement with the maximum residue limits (MRLs) established by the European Commission for pesticides in wine grapes. Finally, the analysis of 84 red wine samples from the Canary Islands, the Iberian Peninsula, and Cape Verde was carried out, which found the presence of 31 pesticide residues. However, the risk assessment disclosed that despite the large number of pesticides and the concentrations found, which in some cases exceeded the MRLs, the consumption of these wines, without considering a possible cumulative effect, does not entail a risk to the consumers.